Insentif Pajak sebagai Pemicu Kepatuhan Pajak: Mengungkap Misteri Kepatuhan Pajak di Indonesia - Hengky Pratama; Aesonya Sarah Yohana Ate; Priscilla Kartika Siagian; Hespin Marcelena; Dielanova Wynni Yuanita (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Using criteria including tax incentives, tax knowledge, moral integrity, and tax sanctions, this study seeks to experimentally analyze the elements that impact MSME taxpayer compliance. This study applies compliance theory. Participants in this study were individual taxpayers from different regions of Indonesia who met the inclusion criteria determined by a battery of statistical tests conducted using SEM-PLS. Tax incentives can help MSME taxpayers become more tax compliant by enhancing their tax literacy and honesty, according to this study's findings. One way to encourage more compliance among MSME taxpayers is to implement strict tax sanctions. One way the government might encourage more compliance from MSMEs is by offering tax incentives. It is crucial to undertake this study in order to ascertain the efficacy of tax incentive programs implemented by the Indonesian government in empowering MSME and to enhance compliance among MSME taxpayers by analyzing the effects of these programs on MSME taxpayers. The study's findings will provide policymakers with useful criticism and recommendations for the long-term improvement of MSME welfare.